16-channel photonic solver for optimization problems on a silicon chip - Jiayi Ouyang; Shengping Liu; Ziyue Yang; Wei Wang; Xue Feng; Yongzhuo Li; Yidong Huang (Chip)
A programmable photonic solver for quadratic unconstrained binary optimization (QUBO) problems is demonstrated with a hybrid optoelectronic scheme, which consists of a photonic chip and an electronic driving board. The photonic chip is employed to perform the optical vector-matrix multiplication (OVMM) to calculate the cost function of the QUBO problem, while the electronic processor runs the heuristic algorithm to search for the optimal solution. Due to the parallel and low-latency propagation of lightwaves, the calculation of the cost function can be accelerated. The photonic chip was fabricated on the silicon on insulator (SOI) substrate and integrated 16 high-speed electro-optic modulators, 88 thermo-optic phase shifters, and 16 balanced photodetectors. The computing speed of the photonic chip is 1.66 TFLOP/s. As a proof of principle, two randomly generated 16-dimensional QUBO problems are solved with high successful probabilities. These results present the potential of fast-solving optimization problems with integrated photonic systems.